Cultural Identity and Virtual Consumption in the Mimetic Homeland: A Case Study of Chinese Generation Z Mobile Game Players - Shiyi Zhang; Zengyu Li; Xuhua Chen (Social Sciences)
In the digital age, mobile games have become a new frontier for cultural identity and virtual consumption among Chinese Generation Z youth. With the development of the internet, users have gradually adapted to the coexistence of virtual and real identities, enriching the “small society” within games. However, virtual consumption and its underlying driving mechanisms have not received sufficient attention. Through interviews with 20 young people of Chinese Generation Z, this study argues that virtual consumption is not only about material consumption but also serves as a link between emotions and identity. In China’s increasingly atomised society, the idea of the “mimetic homeland” has become an essential interactive domain for Generation Z in the digital age. It offers individuals a dynamic space to engage with their cultural identity and sustain emotional resonance amid fragmented social conditions. In the “mimetic homeland”, game content, broadcaster charm, symbolic consumption, and player creation intertwine, allowing mobile games to create a diverse cultural identity mechanism. This mechanism rekindles players’ recognition of cultural identity and provides them with spiritual support. In mobile games, players continuously produce and consume cultural identity, using digital means to shape and spread spiritual consciousness symbols, ultimately achieving cultural identity commodification.